(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
Background: Vitamin D deficiency due to varying sunlight exposure in adult population is one of the prevalent medical conditions worldwide. Objectives: To investigate the prevalence of and the seasonal influence on vitamin D deficiency among the people residing in the Chattogram division of Bangladesh. Methods: The serum 25-hydroxy vitamin D (25-OHD) was assessed by the chemiluminescence method. To investigate the seasonal impact three distinct seasons were broadly categorized winter, summer, and rainy seasons. Results: This observational study analyzed serum 25-OHD data from 969 participants, comprising 777 adults (80%) and 192 children (20%). Among the adults, 77% were female and 23% male, while in the child group, 53% were female and 47% male. A significant positive correlation was found between age and serum 25-OHD (p=.001**). Comparison based on gender, adult males showed relatively higher mean serum 25-OHD levels (18.79 ± 11.02 ng/mL) than females (16.69 ± 10.16 ng/mL). The varying degrees of vitamin D deficiency (mild, moderate, severe) were significantly associated with the gender of the adult participants (Χ2 (2, N = 712) =5.994, p = 0.05*) as well. Seasonal comparison in women showed a better status of vitamin D3 (significantly higher, mean difference: 2.16, p = 0.047*) in the rainy season than winter. Conclusion: The highest average serum vitamin D3 levels were observed during the rainy season, while the lowest occurred in winter, with significant seasonal variation in 25-OHD levels found only in females. This suggests that seasons may influence vitamin D deficiency status. Bangladesh J. Nuclear Med. 28(1): 114-118, 2025